2010
DOI: 10.1590/s1982-56762010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Development of classification criteria for resistance to soybean rust and differences in virulence among Japanese and Brazilian rust populations

Abstract: In recent years soybean rust, caused by Phakopsora pachyrhizi has become one of the most serious threats to soybean production in Brazil. Breeding lines and varieties have been selected for resistance to soybean rust in Asia. However, differences in virulence between Asian and Brazilian rust populations should be considered in order to select and use resistant resources from Asia. Here, we suggest criteria for distinguishing resistant from susceptible types by the analysis of four resistance characters: freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 23 publications
6
105
1
4
Order By: Relevance
“…By using such differences in the host-plant responses, a method of evaluating soybean resistance to P. pachyrhizi and assessing the pathogenicity of P. pachyrhizi has been established (Akamatsu et al 2013, Yamanaka et al 2010). In addition, P. pachyrhizi samples from Argentina, Provinces of Argentina, states of Brazil, and departments of Paraguay are shown on each map.…”
Section: Introductionmentioning
confidence: 99%
“…By using such differences in the host-plant responses, a method of evaluating soybean resistance to P. pachyrhizi and assessing the pathogenicity of P. pachyrhizi has been established (Akamatsu et al 2013, Yamanaka et al 2010). In addition, P. pachyrhizi samples from Argentina, Provinces of Argentina, states of Brazil, and departments of Paraguay are shown on each map.…”
Section: Introductionmentioning
confidence: 99%
“…The initial symptoms of ASR are chlorosis of polygonal shape in the leaves delimited by the veins that evolve later to brown lesions where uredia containing numerous urediniospores arise (Sinclair and Hartman, 1999). ASR is a difficult disease to control due to the highly aggressive nature of the pathogen and the absence of cultivars with satisfactory levels of resistance (Yamanaka et al, 2010). The greatest damage caused by ASR is the early defoliation of the plants (Li et al, 2010), which results in a reduction in the number of pods, number…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the racespecific resistance is often of short duration, especially in biotrophic pathogens like P. pachyrhizi, with high virulence variability. Varieties with two pyramided resistance genes tend to express greater durability of resistance than varieties with a single gene [73,74]. Lemos et al [75] and Yamanaka et al [76] reported that a variety with three resistance genes (Rpp2, Rpp4 and Rpp5) showed significantly higher resistance than its ancestor, showing that pyramiding strategy is effective to increase the rust resistance.…”
Section: Resistancementioning
confidence: 99%